Recognition of Same Sex Marriages in India: Need of Expansion of Personal Liberty in the Light of Constitutional Morality - Irale, Vikram; Pednekar, Kiranmayi (Journal of Constitutional Law and Jurisprudence, 2024)
History repeats itself; therefore, we will wait for the NAZ Foundation case to do so again. In recent years, there has been a notable movement in the global perspective toward the acceptance and acknowledgement of the rights of individuals who identify as LGBTQ+. In India, same-sex marriage legalization is still a contentious issue, which emphasizes the need for a more comprehensive comprehension of human liberty in light of constitutional morality. According to the Constitutional Morality Rule of Law, the governmental apparatus must protect the rights to social justice, equality, due process, individual liberty, and freedom of expression. In addition, legal recognition of SSM is required for social status, the removal of social stigma, legal protections, economic benefits, emotional well-being, inheritance, insurance, and health coverage. The "right to be let alone" is only one aspect of the right to privacy; it goes well beyond that. Included now are the notions of geographical privacy and decisional privacy, often known as privacy of choice. It includes the autonomy to choose for oneself in fundamental decisions. "Law" is a social change instrument. Laws evolve together with society. It should be keeping in with the needs of the society.